ON THE SOLUTION OF THE EQUATION $\dfrac{5}{k}=\dfrac{1}{x}+\dfrac{1}{y}+\dfrac{1}{z}$ ON THE SET OF NATURAL NUMBERS $N\{60n+1, n \in N\}$ - Aslanyan, E.Kh. (Proceedings of the YSU A: Physical and Mathematical Sciences, 2013)
In the present paper it is shown that for every number $k ot\equiv 1\pmod{60},$ the equation $\dfrac{5}{k}=\dfrac{1}{x}+\dfrac{1}{y}+\dfrac{1}{z}$ has at least one solution $(x, y, z)\in N.$
Keywords: Serpinsky’s hypothesis